Literary tourism - Vitić-Ćetković, Andriela (Annales. Series historia et sociologia, 2020)
Increasing competition on the global tourism market forces numerous tourist destinations to create a specific image and diversify their offers through innovative and sustainable tourism products. In view of this, there is a range of possibilities for utilizing historical resources, tangible and intangible cultural heritage, including travel literature, which has not been considered in Montenegro thus far in the context of potentials for enhancing the tourist offer. This paper is focusing on the research of travel literature by 19th century authors from Russia who wrote about Cetinje and Montenegro, as well as the possibilities of creating a destination image and diversified experience for specific market niches, primarily the tourists from Russia who have been among the most numerous in Montenegro. The expected outcome of the research is to point out the importance of valorisation of Russian traveler literature in the context of creating a destination image. Considering the negative propaganda of a part of the media in Russia when Montenegro entered NATO in 2017, it is expected that this Balkan and Adriatic country, whose primary business is tourism, will have to identify and acquire state-of-the-art modalities for attracting new target segments from the Russian Federation. In this paper, literary tourism with the concepts of town - museum, town of books and storytelling, as marketing communications tools, are proposed to promote the revival and valorization of historical events, historical figures and Cetinje's former image in the positioning of the tourism destination, also in the conte xt of sustainable tourism development.
Keywords: Cetinje; Črna Gora; destination image; destination positioning; heritage; kulturna dediščina; literarni turizem; literary tourism; Monte Negro; podoba destinacije; potopisi; storytelling; travel literature; umeščanje destinacije; zgodbarjenje